2019
DOI: 10.1111/jdv.15651
|View full text |Cite
|
Sign up to set email alerts
|

The association between the socioeconomic status and anxiety–depression comorbidity in patients with psoriasis: a nationwide population‐based study

Abstract: Background Numerous studies have indicated that comorbid anxiety and depression are associated with a more severe course of illness. Yet generally, the study of the effect of psoriasis on patients’ mental health has considered anxiety and depression to be separate states. Objective To measure the association between psoriasis and anxiety, depression and anxiety–depression co‐occurrence among patients according to their socioeconomic statuses (SES). Methods A nationwide population‐based study of psoriasis patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
2
10
0
1
Order By: Relevance
“…The logistic regression models confirmed HS as being independently associated with schizophrenia, after controlling for smoking and SES. These findings join other studies which reported co‐occurrence of dermatological conditions with severe psychiatric disorders such as anxiety and depression, which are also argued to be associated with schizophrenia . Although previous studies have reported a marginally significant association between HS and schizophrenia ( P = 0.09), these studies failed to include socioeconomic issues or account for the role of tobacco, factors which are highly associated with both disorders.…”
Section: Discussionsupporting
confidence: 75%
“…The logistic regression models confirmed HS as being independently associated with schizophrenia, after controlling for smoking and SES. These findings join other studies which reported co‐occurrence of dermatological conditions with severe psychiatric disorders such as anxiety and depression, which are also argued to be associated with schizophrenia . Although previous studies have reported a marginally significant association between HS and schizophrenia ( P = 0.09), these studies failed to include socioeconomic issues or account for the role of tobacco, factors which are highly associated with both disorders.…”
Section: Discussionsupporting
confidence: 75%
“…The following background information was collected for each study participant: age (year of birth), gender, marital status (married/not married) and socioeconomic status (low/medium‐high). Socioeconomic status was based on the 2008 Israel National Census which calculates socioeconomic status as an index using a combination of social services records, local district and current address 10,11 . We also recorded the presence of obesity, defined as body mass index (BMI) ≥30, diabetes and smoking status (smoker/nonsmoker).…”
Section: Methodsmentioning
confidence: 99%
“…Bitan et al [ 52 ] showed that respondents with low self-esteem (measured with SES) also experienced overlapping anxiety and depression due to their skin disease (psoriasis) ( p = 0.001).…”
Section: Discussionmentioning
confidence: 99%